How Does Sustainable Halal Fashion Support the Slow Fashion Trends? - Alivian, Ilham; Rohim, Ade Nur (Department of Sharia Economic Law, Faculty Sharia and Law, UIN Sunan Gunung Djati Bandung, 2024)
The worldwide fashion business is seeing swift expansion, but, the adoption of rapid fashion has detrimental effects on ecological sustainability. Sustainable halal fashion, which emphasises quality, sustainability, and ethical values, offers a solution to address this. This study looks at how sustainable halal fashion can strengthen the slow fashion trend and proposes strategic steps for its development. This research employs a qualitative approach to literature study, gathering information from books, articles, and mass media. The results show that sustainable halal fashion contributes to slow fashion and has potential to develop sustainably by increasing public understanding, developing local raw materials, increasing production efficiency, efficiently utilizing supplies and reducing wastage in the manufacturing process., building collaboration. The conclusion is that sustainable halal fashion provides an innovative solution to overcome the fashion industry's negative impact and strengthen the slow fashion trend.